Faith in times of crisis: The moderating role of religious belief on happiness and life effectiveness among Malaysian university students - Getrude Cosmas; Eric Manuel Torres (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
This study investigates how religious faith moderates the relationship between happiness and life effectiveness among university students in Sabah, Malaysia, during the COVID-19 pandemic. The research aims to address the growing psychological challenges faced by youths by exploring whether internal resources such as happiness and faith can strengthen life competencies in times of crisis. A quantitative research design was employed using a cross-sectional online survey distributed to students from public and private universities in Sabah. The survey collected data from 521 participants using validated instruments to measure happiness, religious faith, and life effectiveness. The data were analysed using hierarchical regression analysis to assess the moderating effect of religious faith. The findings show that happiness significantly predicts life effectiveness, accounting for 31.3% of the variance. Religious faith adds an additional 2.7%, while the interaction between happiness and faith contributes a further 1.0%, indicating a significant moderating effect. Students who reported both high happiness and strong faith demonstrated higher levels of emotional control, time management, and initiative. The study implies that cultivating both emotional well-being and religious faith can enhance youth resilience and functional effectiveness, especially during crises. These findings have practical applications in mental health programming and student development initiatives, particularly in multicultural settings like Sabah. This study offers a novel contribution by empirically testing the moderating role of religious faith in the happiness–life effectiveness relationship—a dimension rarely explored in previous literature. It expands current understanding of psychosocial dynamics among young people in culturally diverse societies.